Energy-efficiency based buffer-aided relay selection scheme in SWIPT - Xinlong HONG; Xiaorong XU; Yingbiao YAO (Dianxin kexue)
Aiming at the problem of buffer-aided half-duplex (HD) relay selection in simultaneous wireless information and power transfer(SWIPT) with energy constraint,energy-efficiency priority based buffer-aided relay selection scheme in SWIPT was investigated.Moreover,SWIPT system energy efficiency was studied,and an appropriate mathematical model was constructed to perform energy efficiency based buffer-aided optimal receive/transmit relay selection in SWIPT.Numerical results show that the proposed scheme effectively reduces SWIPT outage probability and achieves the tradeoff between energy efficiency and outage performance in buffer-aided SWIPT.